The alluaudite-like arsenate NaCaMg(3)(AsO(4))(3) - Haj Abdallah, Anissa (International Union of Crystallography, 2008)

(untitled)
The title compound, sodium calcium trimagnesium tris(arsenate), an alluaudite-like arsenate, was prepared by solid-state reaction at high temperature. The structure is built up from edge-sharing MgO(6) octahedra in chains associated with the AsO(4) arsenate groups. The three-dimensional network leads to two different tunnels occupied statistically by Na(+) and Ca(2+). One As and one Mg atom lie on twofold rotation axes; one Na and one Ca are disordered over two sites with occupancies of 0.7 and 0.3 and these sites lie on a twofold rotation axis and an inversion centre, respectively.